2015
DOI: 10.3390/toxins7051702
|View full text |Cite
|
Sign up to set email alerts
|

Perfringolysin O: The Underrated Clostridium perfringens Toxin?

Abstract: The anaerobic bacterium Clostridium perfringens expresses multiple toxins that promote disease development in both humans and animals. One such toxin is perfringolysin O (PFO, classically referred to as θ toxin), a pore-forming cholesterol-dependent cytolysin (CDC). PFO is secreted as a water-soluble monomer that recognizes and binds membranes via cholesterol. Membrane-bound monomers undergo structural changes that culminate in the formation of an oligomerized prepore complex on the membrane surface. The prepo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 124 publications
(244 reference statements)
0
53
1
Order By: Relevance
“…These results suggested that some other bacterial components also contribute to this phenomenon. Perfringolysin O, a cholestrerol-dependent cytolysin, is known as a major toxin produced by C. perfringens type A strains 25 26 . Purified perfringolysin O has been shown to be cytotoxic to polymorphonuclear leukocytes and macrophages 27 28 29 .…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that some other bacterial components also contribute to this phenomenon. Perfringolysin O, a cholestrerol-dependent cytolysin, is known as a major toxin produced by C. perfringens type A strains 25 26 . Purified perfringolysin O has been shown to be cytotoxic to polymorphonuclear leukocytes and macrophages 27 28 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that CPA plays an essential role in gas gangrene through the use of cpa mutants, which display demonstrably reduced virulence in a mouse model (Awad et al, 1995). PFO, encoded by the pfoA gene, is identified as a lethal pore-forming cholesterol-dependent cytolysin (CDC) produced by nearly all C. perfringens strains (Verherstraeten et al, 2015). PFO can bind to cholesterolcontaining membranes and oligomerize into a pore complex to lyse cells (Stevens and Bryant, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…3A). The three candidates that exhibited the highest reduction in spheroid size were azurin (28), theta-toxin (29), and hemolysin E (30). The former is a proapoptotic protein, whereas the latter two are pore-forming toxins, of which theta-toxin has not yet been studied as an engineered bacterial therapeutic to our knowledge.…”
Section: Establishing a Stable Bacteria Co-culture System In Multicelmentioning
confidence: 99%